Drug utilization pattern in patients of upper respiratory tract infections in pediatrics outpatient department at a tertiary care hospital - Hotwani, Jitendra H.; Tathe, Ankita V.; Save, Sushma (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Upper respiratory tract infections are the most common and frequently occurring infections in the pediatric population. These infections include conditions like common cold, laryngitis, pharyngitis, tonsillitis, acute rhinitis, acute rhinosinusitis and acute otitis media. Young children have an average of 6-8 colds per year, however 10 -15% of children have at least 12 infections per year. This study concentrates on prescription pattern of Upper Respiratory Tract Infections in children. primary objective was to study the prescription pattern of drugs used in URTI in pediatric outpatient department and the secondary objective was to determine whether the drugs being prescribed comply with those listed in the National list of essential medicines. Methods: This study was a Cross-sectional, observational study conducted at the Pediatric Outpatient Department in a tertiary care hospital, India. The data was collected from patients visiting Pediatrics OPD from June 2021 to December 2021 after taking written informed consent. Sample size was calculated to be 303. Results: Total 943 drugs were prescribed for 303 patients with an average of 3.11±1.15 drugs per prescription. Most common class of drugs prescribed was Antipyretics of which Paracetamol was the most common drug. Antibiotics were prescribed for 19.80% patients & combination of Amoxicillin and Clavulanic acid was the most common antibiotic prescribed. 68.29% drugs were prescribed by generic name. 43.16% drugs were prescribed from National List of Essential Medicines 2015. Conclusions: The study revealed that the majority of children suffering from URTI were below 5 years of age. Our study highlighted the prescribing.